Quantifying Chaos by Various Computational Methods. Part 2: Vibrations of the Bernoulli–Euler Beam Subjected to Periodic and Colored Noise; Entropy; Vol. 20 - Awrejcewicz J. Jan; Krysko A. V. Anton Vadimovich; Erofeev N. P. Nikolay Pavlovich; Dobriyan V. V. Vitaly Vyacheslavovich; Barulina M. A. Marina Aleksandrovna; Krysko V. A. Vadim (2018, 2018)
Title screen